Pulp stones and kidney stones-related gene: An investigation of single nucleotide polymorphisms in the gene encoding parathyroid hormone - Prescila Mota de Oliveira Kublitski; Bruna de Souza Romano; Vania Gomes Moraes; Manoel Damião Sousa-Neto; Lívia Azeredo Alves Antunes; Erika Calvano Küchler; Leonardo Santos Antunes; João Armando Brancher; Edgard Michel-Crosato; Marilisa Carneiro Leão Gabardo (Heliyon)
Introduction: Pulp stones (PS), whose origins remain unclear, present a challenge for clinical practice in Endodontics. Similar to other calcifications, a relationship with parathyroid hormone is hypothesized. Purpose: The aim of this study was to investigate the association between the presence of PS and kidney stones (KS) and single nucleotide polymorphisms (SNPs) in the parathyroid hormone (PTH) gene, which is related to KS. Methods: This cross-sectional study included adults of both sexes, divided into groups: with PS and without PS. PS diagnosis was based on radiographic evaluation. Saliva samples were collected from all participants, and prior history of KS was recorded. The samples were processed, and genomic DNA was used to genotype the rs694, rs6256, and rs307247 SNPs. The Hardy-Weinberg equilibrium was assessed using the Chi-square test. Genotypic and allelic profiles under additive, dominant, and recessive models were evaluated using a univariate logistic regression model and the Wald test, with analyses conducted in SPSS® version 23.0. Additionally, Fisher's exact test was used to compare the haplotype frequencies. Statistical significance was set at 5 %. Results: The study included 63 patients with PS and 54 without PS, with a mean age of 32.5 years. No statistically significant association was observed between the groups regarding the presence of KS. Allelic and genotypic analyses revealed no significant association (P > 0.05) between the presence of PS and SNPs analyzed in the groups studied. Conclusion: None of the SNPs studied in the gene encoding PTH were associated with PS or KS.